Saturated-blue-emitting [3+2+1] coordinated iridium(iii) complexes for vacuum-deposited organic light-emitting devices. Issue 39 (16th September 2022) - Zhang, Meng; Ng, Maggie; Wu, Chengcheng; Tong, Kai-Ning; Li, Wansi; Wu, Yuan; Yang, Chen; Wang, Min; Tang, Man-Chung; Wei, Guodan
Abstract : The saturated-blue phosphorescent OLEDs based on the [3+2+1] coordinated iridium(iii ) complexes bearing the phenyl-3H-imidazo[4, 5- b ]pyridine-based (C^C) bidentate ligands, demonstrating an EQE of 11.2% and CIE ( x, y ) coordinates of (0.16, 0.07). Abstract : A new class of deep-blue phosphorescent [3+2+1] coordinated iridium(iii ) complexes containing phenyl-3 H -imidazo[4, 5- b ] pyridine-based (C^C) bidentate ligands have been synthesized, characterized, and applied as phosphorescent dopants in the fabrication of vacuum-deposited organic light-emitting devices (OLEDs). The manipulation of the relative bulkiness of the C^C ligands is the key to control the emission energies in solid-state thin films, ranging from 415 to 470 nm. Taking advantages of the intra-ligand charge transfer nature of the emissive state, these complexes display short excited-state lifetimes in the sub-nanosecond regime of 0.3 to 1.1 μs, yielding high radiative decay rate constants on the order of up to 10 6 s −1 . High-performance vacuum-deposited deep-blue-emitting OLEDs have been fabricated based on these complexes, demonstrating an external quantum efficiency (EQE) of 11.2% and Commission International de L'Eclairage (CIE ( x, y )) coordinates of (0.16, 0.07), making them the deepest blue emitters for this class of new [3+2+1] Ir phosphorescent materials.